MPEG-icariin nanoparticles for treating myocardial ischaemia. Issue 1 (4th December 2019) - Zheng, Yongqiang; Lu, Lingli; Yan, Zhengli; Jiang, Sufang; Yang, Shanyi; Zhang, Yingzi; Xu, Kangwei; He, Chunlian; Tao, Xiaojun; Zhang, Qiufang
Abstract: Icariin (ICA), a major active ingredient from Chinese medicine, has unique pharmacological effects on ischaemic heart disease. However, its hydrophobic property limits its administration and leads to poor efficacy. This work aimed to change its hydrophobic property and improve the treatment efficacy. We designed a new nano-drug to increase the ICA delivery. ICA was modified with hydrophilic polyethylene glycol monomethyl ether (mPEG) by a succinic anhydride linker to form a polyethylene glycol-icariin (mPEG-ICA) polymer. The structure of this polymer was identified by Fourier transform infrared spectroscopy and nuclear magnetic resonance spectroscopy. The content of ICA in the polymer was 32% as detected by ultraviolet spectrophotometry. mPEG-ICA nanoparticles, of 143.3 nm, were prepared by the dialysis method, and zeta potential was 0.439 mV by dynamic light scattering. The nanoparticles had a spherical shape on transmission electron microscopy. In media with pH 7.4 and 6.8, ICA release from mPEG-ICA nanoparticles after 72 h was about 0.78% and 64.05%, respectively, so the ICA release depended on the release media pH. On MTT and lactate dehydrogenase activity assay, mPEG-ICA nanoparticles could reduce cell damage induced by oxgen-glucose deprivation. Hoechst 33258 staining and TUNEL and AnnexinV-FITC/PI double staining showed that ICA nanoparticles could increase the activity of H9c2 cardiomyocytes under oxgen-glucose deprivation conditions by decreasing apoptosis. ICA modified by hydrophilic mPEG could improve its efficacy.